Photoperiod-Dependent Effects of 4-tert-Octylphenol on Adherens and Gap Junction Proteins in Bank Vole Seminiferous Tubules - Anna Hejmej; Malgorzata Kotula-Balak; Katarzyna Chojnacka; Paulina Kuras; Marta Lydka-Zarzycka; Barbara Bilinska (International Journal of Endocrinology, 2013)
In the present study we evaluated in vivo and in vitro effects of 4-tert-octylphenol (OP) on the expression and distribution of adherens and gap junction proteins, N-cadherin, β-catenin, and connexin 43 (Cx43), in testes of seasonally breeding rodents, bank voles. We found that in bank vole testes expression and distribution of N-cadherin, β-catenin, and Cx43 were photoperiod dependent. Long-term treatment with OP (200 mg/kg b.w.) resulted in the reduction of junction proteins expressions (P<0.05, P<0.01) and their delocalization in the testes of males kept in long photoperiod, whereas in short-day animals slight increase of Cx43 (P<0.05), N-cadherin, and β-catenin (statistically nonsignificant) levels was observed. Effects of OP appeared to be independent of FSH and were maintained during in vitro organ culture, indicating that OP acts directly on adherens and gap junction proteins in the testes. An experiment performed using an antiestrogen ICI 182,780 demonstrated that the biological effects of OP on β-catenin and Cx43 involve an estrogen receptor-mediated response. Taken together, in bank vole organization of adherens and gap junctions and their susceptibility to OP are related to the length of photoperiod. Alterations in cadherin/catenin and Cx43-based junction may partially result from activation of estrogen receptor α and/or β signaling pathway.